Obesity Bias in the School Setting: A Brief Report - José I. Baile; María J. González-Calderón; María F. Rabito-Alcón (MDPI AG, 2022)
Obesity bias is one of the main psychosocial consequences experienced by people who are overweight and people with obesity. Therefore, its study, especially during childhood, has become an emerging objective. The aim of this study is to examine obesity bias in children in the school setting. In total, 171 primary school students (Mean age: 10.68; SD: 0.63) from a school in Madrid (Spain) filled out a survey in which they indicated whether they would choose a classmate with obesity with whom they would carry out academic, social, and leisure activities. The rejection ratios of peers with obesity and other personal characteristics such as gender, nationality, or ethnicity were compared. The results indicate that more than half of the participants would not choose a partner with obesity to carry out any of the three activities suggested, and that obesity was the personal characteristic that elicited the highest rate of rejection, especially among females. The possible explanations for these findings are discussed, as well as why the school setting should be a nonaggressive but protective environment for children with obesity.